Impacto da pandemia da Covid-19 no nível de atividade física e saúde mental de idosos - Rosa, Elise Rumpel da (2022)
The rapid and uncontrolled spread of COVID-19 has caused fear around the world. Measures had to be taken to try to contain the contagion, such as strict hygiene habits, mask wearing and social distance. The population considered the most vulnerable to the disease were the elderly. Thus, the aim of this study is to analyze the impact of the COVID-19 pandemic on the physical activity (PA) level and mental health of the elderly. It is a cross-sectional study characterized as correlational descriptive research. The target population of this study are elderly participants in senior living groups, in Santa Maria-RS and linked to the Integrated Center for Studies and Support for the Elderly (NIEATI) of the Physical Education and Sports Center (CEFD) of the Federal University of Santa Maria (UFSM). For data collection, a questionnaire with characterization questions was applied, as well as the International Physical Activity Questionnaire (IPAQ)-short version to estimate the PA level, and the Generalized Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire (PHQ-9), both validated for the Portuguese language, to assess mental health. The questionnaires were applied by interview. The collected data were treated through descriptive statistical analysis, with central tendency and dispersion measures. To assess normality, the Kolmogorov-Smirnov test was used. Correlation was evaluated by Spearman's correlation test, and to compare the results of different periods, Wilcoxon’s test was applied. There was a statistically significant difference (p<0.05) in the variables PA at work and PA at leisure, which decreased during the pandemic. Sedentary behavior time, and symptoms of anxiety and depression were significantly higher during the pandemic. It was concluded that there was a significant impact of the pandemic on mental health and physical activity levels of the elderly. Sedentary behavior, anxiety and depression during the pandemic increased when compared to the period before the pandemic. However, no relationship was observed between the level of physical activity and mental health of the elderly surveyed.